Between Abstraction and Concreteness. Functions and Strategies of Theory-driven Qualitative Research Zwischen Abstraktion und Konkretion.Funktionen und Strategien Theoretischer Empirie - Antony, Alexander (Zeitschrift für Soziologie, 2026)
The debate surrounding theory-driven qualitative research (Theoretische Empirie) has been an important catalyst for discussions about the relationship between social theory and empirical practice in qualitative social science. This article advances that discourse by elaborating on the practical implications and potential of Theoretische Empirie. In doing so, it offers a systematic contribution to the question of how this approach can be put into practice. The article centers on a discussion of three key issues: (1) the empirical irritation of theoretical assumptions, (2) the theoretical construction of the object of study, and (3) the relationship between theory and methodological practice. For each issue, it outlines concrete strategies and scenarios through which Theoretische Empirie can be realized and rendered applicable as a research strategy. The article argues that only through a methodological explication of its practical possibilities can Theoretische Empirie become manageable and fruitfully employed within qualitative research.
CRIS-Team Scopus Importer:2026-03-06
Keywords: Methodologie; Qualitative Sozialforschung; Sozialtheorie; Soziologische Theorie; Theoretische Empirie